CARA EFEKTIF DALAM MENGEMBANGKAN DESA MENJADI DESA WISATA: STUDI KASUS DESA BAYAN KABUPATEN LOMBOK UTARA: Development Strategy of Bayan Village As A Tourism Village in North Lombok District - Rizal Kurniansah (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Bogor, 2024)
The purpose of this study is to determine the tourism potential of bayan village, the form of local community participation, and formulate a good strategy in developing bayan village into a tourist village in North Lombok Regency. The type of research is qualitative research, data collection methods are observation, interviews, literature study, and documentation. Data analysis is SWOT analysis. Based on the results of the research conducted, the following strategies are produced Utilising technological advances in marketing and promoting Bayan Village, Developing a variety of rural tourism products based on the uniqueness of local potential, Creating a brand image of Bayan Village tourism destinations, Community empowerment through training, Developing and arranging supporting facilities in Bayan Village, Establishing Calender Of Events, Increasing Cooperation with travel agencies and creating more tour packages to Bayan Village, Creating special rules and policies in tourism development, Cooperating with related agencies in tackling environmental damage, implementing a healthy village to meet CHSE criteria, Conducting counselling to the local community, Increasing supervision of tourism activities, Maximising the Tourism Development Budget through cooperation, and Increasing public awareness of tourism awareness and sapta pesona.